Chitosan/hydroxyapatite composite bone tissue engineering scaffolds with dual and decoupled therapeutic ion delivery: copper and strontium. Issue 40 (24th September 2019) - Gritsch, Lukas; Maqbool, Muhammad; Mouriño, Viviana; Ciraldo, Francesca E.; Cresswell, Mark; Jackson, Philip R.; Lovell, Christopher; Boccaccini, Aldo R.
Abstract : Porous composite scaffolds with decoupled ion release of copper and strontium were fabricated and characterized: a reproducible and cost-effective approach to obtain constructs with tailored release profiles and promising biological properties. Abstract : Therapeutic metal ions are a family of metal ions characterized by specific biological properties that could be exploited in bone tissue engineering, avoiding the use of expensive and potentially problematic growth factors and other sensitive biomolecules. In this work, we report the successful preparation and characterization of two material platforms containing therapeutic ions: a copper(ii )–chitosan derivative and a strontium-substituted hydroxyapatite. These biomaterials showed ideal ion release profiles, offering burst release of an antibacterial agent together with a more sustained release of strontium in order to achieve long-term osteogenesis. We combined copper(ii )–chitosan and strontium–hydroxyapatite into freeze-dried composite scaffolds. These scaffolds were characterized in terms of morphology, mechanical properties and bioactivity, defined here as the ability to trigger the deposition of novel calcium phosphate in contact with biological fluids. In addition, a preliminary biological characterization using cell line osteoblasts was performed. Our results highlighted that the combination of chitosan and hydroxyapatite in conjunction with copper and strontium has great potential in the design of novel scaffolds. Chitosan/HA composites can be an ideal technology for the development of tissue engineering scaffolds that deliver a complex arrays of therapeutic ions in both components of the composite, leading to tailored biological effects, from antibacterial activity, to osteogenesis and angiogenesis.